A CONFIRMATORY ANALYSIS OF FOOD SECURITY IN NORTH SUMATERA - Yusri, Mohammad; Tirtayasa, Satria; Siregar, Muhammad Said; Kartaatmaja, R.S. (Jurnal Manajemen dan Agribisnis, 2021)
This study aims to provide empirical evidence and investigations on the development of food security in North Sumatera Province (PSU). This research was conducted in districts/cities in North Sumatera Province. Data collection techniques in this study were secondary data collection (aspects of food production per year in a cycle of two harvests calculated on an average, annual population growth rate and annual rice field area), observation and interviews. The analysis technique using Confirmatory Factor Analysis. The results showed that the trend of food security in the aspect of food production, in the aspect of production value, has generally decreased, so that the fulfillment of food production is only eighty percent and shortages each year are met through imports from other countries. Welfare in the PSU is determined by confirmatory factors with the availability of agricultural land, then population and food security. Keywords: confirmatory analysis, food security, north sumatera, agriculture, starving